PENERAPAN SISTEM KOMPUTERISASI HAJI TERPADU (SISKOHAT) DALAM UPAYA MEMBERIKAN PERLINDUNGAN HUKUM PADA JEMAAH HAJI SEBAGAI KONSUMEN LAYANAN PUBLIK DI KANTOR KEMENTERIAN AGAMA KABUPATEN SANGGAU - NIM. A1012171088, FITRIA AULI WULANDARI (Fakultas Hukum Universitas Tanjungpura, 2023)
ABSTRACTHajj is a worship that completes the pillars of Islam which must be performed once in a lifetime by every Muslim on earth, especially those who are able, both physically, mentally and materially. The specialty of the Hajj pilgrimage for Muslims lies in its implementation which has special rules regarding requirements, pillars and procedures that must be carried out in an orderly manner, including that it can only be done once a year with a limited place and time, namely at the beginning of the month of Shawwal until Eid al-Adha. in Baitullah. To protect the interests of Indonesian citizens abroad (Saudi Arabia), the government is obliged to take an active role in its implementation. Therefore, based on Law Number 8 of 2019 concerning the Implementation of the Hajj and Umrah Pilgrimage, the government through the Indonesian Ministry of Religion regulates regulations regarding the entire process of organizing the Hajj, both at home and abroad. In order to carry out the Hajj pilgrimage activities in a transparent and accountable manner based on the principles of good governance and to protect the rights and interests of Hajj pilgrims, the Ministry of Religion created a large recording system which is the backbone of the government's Hajj pilgrimage, called the Integrated Hajj Information and Computerization System (SISKOHAT ). This system is also implemented at the Sanggau Regency Ministry of Religion Office, which is part of the vertical agency of the Indonesian Ministry of Religion. One of the duties and functions of the Sanggau Regency Ministry of Religion Office is to provide services in the pilgrimage sector in the Sanggau Regency working area.The problem in this research is